(untitled) (Journal of Pathology of Nepal, 2016)
Background: Neoplastic and non-neoplastic urinary bladder lesions are the main reasons for morbidity and mortality throughout the world. Amongst these, urothelial carcinoma is a common primary tumor of urinary bladder (90%). The objective of this study is to determine the profile of various urothelial lesions received in Army Hospital within 5 years of period. Materials and methods: Five years retrospective study of cystoscopic biopsies and radical cystectomy specimens were carried out in Department of Pathology, Army hospital. Results: Out of 53 cystoscopic biopsies and radical cystectomy specimens, 42 were neoplastic and 11 were non neoplastic lesions. Thirty six urothelial carcinomas were observed out of which 20 were high grade urothelial carcinoma and 16 were low grade. Out of 20 high grade urothelial carcinoma, 17 had muscle invasion and 3 had invasion upto lamina propria. Of 16 low grade urothelial carcinoma, 12 were noninvasive, 2 had invasion upto lamina propria and 2 had muscle invasion. Papilloma was the commonest benign lesions found (7.1%) followed by papillary urothelial neoplasms of low malignant potential (PUNLMP) (2.4%) and hemangioma (2.4%). Conclusion: This article have highlighted upon the importance of histopathological study in evaluating urinary bladder lesions. Also, it has helped in determining that neoplastic lesions were more common than non-neoplastic lesions as seen in our study. A great majority of neoplastic lesions were of urothelial origin. Cystoscopic studies and biopsies help in early detection of bladder neoplasms and they form the mainstay of the diagnosis and follow up.